Bioinformatics Updated Features and Applications - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2016)
An interdisciplinary bioinformatics science aims to develop methodology and analysis tools to explore large-volume of biological data using conventional and modern computer science, statistics, and mathematics, as well as pattern recognition, reconstruction, machine learning, simulation and iterative approaches, molecular modeling, folding, networking, and artificial intelligence. Written by international team of life scientists, this Bioinformatics book provides some updates on bioinformatics methods, resources, approaches, and genome analysis tools useful for molecular sciences, medicine and drug designs, as well as plant sciences and agriculture. I trust chapters of this book should provide advanced knowledge for university students, life science researchers, and interested readers on some latest developments in the bioinformatics field.